Finding underlying genetic mechanisms of two patients with autism spectrum disorder carrying familial apparently balanced chromosomal translocations. (11th March 2021) - Toraman, Bayram; Bilginer, Samiye Çilem; Hesapçıoğlu, Selma Tural; Göker, Zeynep; Soykam, Hüseyin Okan; Ergüner, Bekir; Dinçer, Tuba; Yıldız, Gökhan; Ünsal, Serbülent; Kasap, Burak Kaan; Kandil, Sema; Kalay, Ersan
Abstract: Background: Genetic etiologies of autism spectrum disorders (ASD) are complex, and the genetic factors identified so far are very diverse. In complex genetic diseases such as ASD, de novo or inherited chromosomal abnormalities are valuable findings for researchers with respect to identifying the underlying genetic risk factors. With gene mapping studies on these chromosomal abnormalities, dozens of genes have been associated with ASD and other neurodevelopmental genetic diseases. In the present study, we aimed to idenitfy the causative genetic factors in patients with ASD who have an apparently balanced chromosomal translocation in their karyotypes. Methods: For mapping the broken genes as a result of chromosomal translocations, we performed whole genome DNA sequencing. Chromosomal breakpoints and large DNA copy number variations (CNV) were determined after genome alignment. Identified CNVs and single nucleotide variations (SNV) were evaluated with VCF‐BED intersect and Gemini tools, respectively. A targeted resequencing approach was performed on the JMJD1C gene in all of the ASD cohorts (220 patients). For molecular modeling, we used a homology modeling approach via the SWISS‐MODEL. Results: We found that there was no contribution of the broken genes or regulator DNA sequences to ASD, whereas the SNVs on the JMJD1C, CNKSR2 and DDX11 genes were the most convincing genetic risk factors for underlying ASD phenotypes. Conclusions: Genetic etiologies of ASD should be analyzed comprehensively by taking into account of the all chromosomal structural abnormalities and de novo or inherited CNV/SNVs with all possible inheritance patterns. Abstract : In the present study, we have comprehensively investigated the genetic etiologies of two autism spectrum disorder (ASD) simplex families that have familial apparently balanced chromosomal translocation findings in the karyotypes of the probands using a whole genome sequencing approach. We mapped the chromosomal breakpoint regions, the protein coding genes that were disrupted as a result of translocations, and identified copy number/single nucleotide variations (CNVs/SNVs) that could be causative for underlying ASD phenotypes. We also performed targeted resequencing of the JMJD1C gene in all 220 ASD patients. Consequently, we found that there was no contribution of the broken genes or regulator DNA sequences to ASD, whereas the SNVs on the JMJD1C, CNKSR2 and DDX11 genes were the most convincing genetic risk factors for underlying ASD phenotypes.